Isolation and Use of Coprothermobacter spp. to Improve Anaerobic Thermophilic Digestion of Grass - Przemysław Liczbiński; Sebastian Borowski; Adriana Nowak (Molecules, 2022)
The isolation of microorganisms was performed from digestate from the process of the anaerobic digestion (AD) of grass after hyperthermophilic pretreatment. The bacterium that was isolated and identified was Coprothermobacter sp. Using the isolated bacteria, an AD process on fresh grass (GB) and pretreated grass (PGB) was carried out with 10% of its addition. The highest methane yield of 219 NmlCH4/gVS was recorded for PGB at 55 °C. In contrast, fresh grass subjected to thermophilic digestion produced only 63 NmlCH4/gVS. Due to the addition of bacteria in the AD process, an increase in the efficiency of hydrogen and methane production was observed in both fresh grass and grass after pretreatment.